Diagnostic Value of Serum Soluble Axl Compared with Alpha-fetoprotein in Hepatocellular Carcinoma: Experience from a Tertiary Center in Bangladesh (Bangladesh Journal of Medicine, 2026)
Background: Hepatocellular carcinoma (HCC) is a leading cause of mortality worldwide. In Bangladesh, early detection is frequently hindered by limited laboratory facilities. Alpha-fetoprotein (AFP) is a well-accepted blood biomarker for HCC detection, but its diagnostic accuracy is suboptimal. Recently, soluble Axl (sAxl), a protein associated with tumor progression, has emerged as a promising biomarker. This study aimed to evaluate the diagnostic performance of serum sAxl in patients with HCC and to compare its accuracy with AFP among Bangladeshi patients with cirrhosis. Methods: A comparative cross-sectional study was conducted in the Departments of Laboratory Medicine and Hepatology at Bangladesh Medical Universityfrom March 2024 to February 2025. Sixty-four participants were enrolled: 32 with HCC and cirrhosis (Group I) and 32 with cirrhosis alone (Group II). Serum sAxl was measured using ELISA, and AFP was measured by chemiluminescent immunoassay. Data analysis was performed with SPSS v26. Diagnostic performance was evaluated using receiver operating characteristic (ROC) analysis, and DeLong’s test was used for area under the curve (AUC) comparison. Results: Median AFP levels were significantly higher in HCC patients (1001 ng/ml) compared to those with cirrhosis (2.8 ng/ml; p< 0.001). Median sAxl levels were also substantially elevated in HCC (146.4 ng/ml) relative to cirrhosis (25.6 ng/ml; p< 0.001). AFP yielded an AUC of 0.689, sensitivity 42.9%, and specificity 81.3%. In contrast, sAxl achieved an AUC of 0.794 (p = 0.018 vs AFP by DeLong’s test), with 75% sensitivity and 84.4% specificity, indicating good diagnostic discrimination between HCC and cirrhosis. Conclusion: Serum sAxl demonstrated greater diagnostic accuracy than AFP in distinguishing HCC from cirrhosis among Bangladeshi patients. Given its noninvasive nature and strong performance, sAxl may serve as a practical biomarker for early HCC detection in resource-limited settings.Bangladesh J Medicine 2026; 37(1): 28-33